Mergers, Foreign Competition, and Jobs: Evidence from the U.S. Appliance Industry - Felix Montag (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Policy choices often entail trade-offs between workers and consumers. I assess how foreign competition changes the consumer welfare and domestic employment effects of a merger. I construct a model accounting for demand responses, endogenous product portfolios, and employment. I apply this model to the acquisition of Maytag by Whirlpool in the household appliance industry. I compare the observed acquisition to one with a foreign buyer. While a Whirlpool acquisition decreased consumer welfare by 250 million, it led to 1,300 fewer domestic jobs lost. Jobs need to be worth above 220,000 annually for domestic employment effects to offset consumer harm.
Keywords: F61; L13; L40; 330